Tata McGraw Hill Education Private Limited - Dixit, Mukund R., (SAGE knowledge. Cases., 2016)
This case presents details of the origin, strategy, and performance of Tata McGraw Hill Education Private Limited. It describes the initiatives of Mr Shukla, Managing Director and Vice President, in maintaining the leadership of the company in a changing environment.